On the effectiveness of self-paced learning - Tullis, Jonathan G.; Benjamin, Aaron S. (Journal of memory and language, 2011)
Metacognitive monitoring and control must be accurate and efficient in order to allow self-guided learners to improve their performance. Yet few examples exist in which allowing learners to control learning produces higher levels of performance than restricting learners’ control. Here we investigate the consequences of allowing learners to self-pace study of a list of words on later recognition, and show that learners with control of study-time allocation significantly outperformed subjects with no control, even when the total study time was equated between groups (Experiments 1 and 2). The self-pacing group also outperformed a group for which study time was automatically allocated as a function of normative item difficulty (Experiment 2). The advantage of self-pacing was apparent only in subjects who utilized a discrepancy-reduction strategy—that is, who allocated more study time to normatively difficult items. Self-pacing can improve memory performance, but only when appropriate allocation strategies are used.